The Diabetic Cardiomyopathy: The Contributing Pathophysiological Mechanisms - Salvatore, Teresa; Pafundi, Pia Clara; Galiero, Raffaele; Albanese, Gaetana; Di Martino, Anna; Caturano, Alfredo; Vetrano, Erica; Rinaldi, Luca; Sasso, Ferdinando Carlo (Frontiers in Medicine, 2021)
Individuals with diabetes mellitus (DM) disclose a higher incidence and a poorer prognosis of heart failure (HF) than non-diabetic people, even in the absence of other HF risk factors. The adverse impact of diabetes on HF likely reflects an underlying “diabetic cardiomyopathy” (DM–CMP), which may by exacerbated by left ventricular hypertrophy and coronary artery disease (CAD). The pathogenesis of DM-CMP has been a hot topic of research since its first description and is still under active investigation, as a complex interplay among multiple mechanisms may play a role at systemic, myocardial, and cellular/molecular levels. Among these, metabolic abnormalities such as lipotoxicity and glucotoxicity, mitochondrial damage and dysfunction, oxidative stress, abnormal calcium signaling, inflammation, epigenetic factors, and others. These disturbances predispose the diabetic heart to extracellular remodeling and hypertrophy, thus leading to left ventricular diastolic and systolic dysfunction. This Review aims to outline the major pathophysiological changes and the underlying mechanisms leading to myocardial remodeling and cardiac functional derangement in DM-CMP.